Police understandings of and responses to a complex vignette of “honour”-based crime and forced marriage - Aujla, Wendy (International Journal of Child, Youth and Family Studies, 2021)
Police understandings of honour-based crimes (HBCs) and forced marriages (FMs) vary in terms of an individual officer’s level of expertise, knowledge, and experience in handling such situations. This study applied constructivist grounded theory approaches to analyze individual interviews with 32 police officers and 14 civilians in police agencies operating in urban and rural settings in Alberta, Canada. Specifically, this paper seeks to answer how police officers and civilians who work in police agencies experience, make sense of, and understand HBCs. Participants received a hypothetical vignette about a young woman who had reached out to the police. The vignette illustrated various forms of abuse by the woman’s father, the involvement of other actors (mother, brother, family friend) and the culmination in an FM. After reading the vignette, participants were asked to respond to six questions. Analysis revealed that both police and civilians recognized the need in the vignette scenario for intervention, while experiencing uncertainty about how to respond. The findings showed that not everyone in policing would be able to identify reliably the need for police intervention, and that investigations could proceed differently depending on the investigator’s level of knowledge and awareness of HBCs and FMs. Police have achieved some successful interventions, but still lack sufficient guidance on how to respond to these crimes. Clear, appropriate policies regarding which cases need to be directed to specialized domestic violence units for follow-up are needed. A significant finding points to the importance of considering cultural sensitivity discourses as well as the impact of cultural and racist stereotypes when responding to situations like the one outlined in the vignette.